Les antonymes : quelques propositions didactiques à partir de la publicité - López Díaz, Montserrat (Canadian Journal of Applied Linguistics, 2011)
The proposal of a didactic approach based on the study of antonym and semantic oppositions in general, through antithetic advertising sentences, stimulates foreign language acquisition for students of intermediate and advanced level. In so doing lexicon is studied in its discursive performance through brief texts, easy to memorize because of both their structural regularity and their rhythm strongly marked. These texts are based on representations shared by the community. Following these examples, students must combine their linguistic and cultural knowledge as well as their creativity and imagination in order to construct an antithetic discourse, so that they can improve their language learning.